2015
DOI: 10.2147/jn.s74145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical neurorestorative progress in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis is a progressive and fatal neurodegenerative disease characterized by progressive paralysis and motor neuron death. In addition to symptomatic managements such as ventilation and nutritional support, neurorestorative therapies have demonstrated anti-neurodegenerative potential and may improve quality of life for patients. Currently, clinical neurorestorative strategies include pharmacological management (granulocyte colony stimulating factor), neuromodulatory intervention (repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The clinical guidelines presented in this document apply more to mature/functionally differentiated cell therapy. To date, clinical trials of treatments based on those categories of cells have been carried out in over 40 countries with documented safety and functional neurological improvement for patients with CNS diseases and damage 74 114 .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical guidelines presented in this document apply more to mature/functionally differentiated cell therapy. To date, clinical trials of treatments based on those categories of cells have been carried out in over 40 countries with documented safety and functional neurological improvement for patients with CNS diseases and damage 74 114 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell therapies have been shown to stabilize or improve neurological functioning and quality of life in patients with amyotrophic lateral sclerosis to some extent for a period of time according to the Amyotrophic Lateral Sclerosis Functional Rating Scale assessment standard. [16][17][18] Farge et al 19 reported that autologous hematopoietic stem cell transplantation is capable of inducing sustained remissions for more than 5 years in patients with severe autoimmune diseases, in particular those with multiple sclerosis, with similar results being shown in other studies. 13,[20][21][22][23][24][25] Although not providing a cure, such therapy may lead to prolonged disease stabilization and attenuate the aggressive course of multiple sclerosis.…”
Section: Routes Used For Cell Therapymentioning
confidence: 58%